(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Lisdiani, Susanto D, Manurung H. 2022. Phytochemical screening and antioxidant activity of methanol extract of Dillenia excelsa leaf. Biodiversitas 23: 3827-3835. The aim of this study was to determine the phytochemical compounds, total flavonoid, and phenolic content, and antioxidant activity of the methanol extract of Dillenia excelsa (Jack) Martelli ex Gilg (or tanikkara) leaves. Sample D. excelsa leaves were obtained from swamp forests in Melintang Village, Muara Wis sub-district, Kutai Kartanegara district, East Kalimantan province, Indonesia. This research includes sample preparation, extraction and maceration, extract concentration using a rotary evaporator, phytochemical test, total phenolic andflavonoid content test, and antioxidant activity test using 2,2-diphenyl-1-picrylhydrazil (DPPH) and Ferric reducing antioxidant power methods (FRAP). The results of this study indicate that the methanolic extract of D. excelsa leaves contains secondary metabolites, including alkaloids, flavonoids, phenolics, triterpenoids, and tannins. The total phenolic content was 181.25 g GAE/g extract, while the total flavonoid content was 36 g QE/g extract. The antioxidant activity of the methanol extract of D. excelsa leaf DPPH method had moderate activity strength with a value of IC50is 145 ppm, while the antioxidant activity of the methanol extract of D. excelsa leaf using the FRAP method has the highest antioxidant activity value at a concentration of 100 ppm with a value of 70.833%. The result indicated that the methanolic extract D. excelsa leaves had many metabolites and potentially an antioxidant.